PERBANDINGAN EFISIENSI TEKNIS INDUSTRI MAKANAN DAN MINUMAN (ISIC 31) SKALA BESAR DENGAN SKALA SEDANG DI INDONESIA - Y. Sri Susilo (Jurnal Ekonomi & Studi Pembangunan, 2005)
This paper aims at identifying and analyzing the rates of technical efficiency in food and beverages industry (ISIC 3 1) in Indonesia. Comparison between the rates in the medium and bigger scale industries is of concerns, using the Cobb-Douglas (CD) production function. Data were collected from the Central Body of Statistics (BPS) for the period 2001. Based on multiple linear regressions using the ordinary least square (OLS) method, conclusion is made that the bigger scale industry t ends to have higher rates of technical efficiency than that of the medium scale in foods and beverages industry.